Influence of oligomer content on viscosity and dynamic mechanical properties of epoxy asphalt binders. (4th July 2022) - Zhao, Ruikang; Jing, Fan; Wang, Rui; Cai, Jun; Zhang, Junsheng; Wang, Qingjun; Xie, Hongfeng
Highlights: Epoxy asphalt binders with three different epoxy oligomer contents have been developed. Viscosity of epoxy asphalt binders decreases in the oligomer content. Allowable construction time of epoxy asphalt binders increased in the oligomer content. Glass transition temperatures of both epoxy and asphalt increases in the oligomer content. The damping ability and tensile strength of epoxy asphalt binders increase in the oligomer content. Abstract: The impact of oligomer content on the viscosity, dynamic mechanical properties and mechanical behaviors of hot-mix epoxy asphalt binders was investigated by Brookfield viscometer, dynamic mechanical analysis and universal testing machine. The viscosity of epoxy asphalt binders during curing decreased in the oligomer content. However, the allowable construction time increased with the oligomer content. The storage modulus of epoxy asphalt binders at the glassy stage decreased in the oligomer content, whereas an opposite trend appeared at the rubbery stage. Epoxy asphalt binders exhibited two glass transition temperatures ( T g s) for both epoxy resin and asphalt, and increased in the epoxy oligomer content. The T g of epoxy of epoxy asphalt binder increased from 30.9 to 42.4 °C when the mass fraction of oligomer increased from 23.5 % to 25.5 %. The damping properties and tensile strength of epoxy asphalt binders increased in the oligomer content, while the elongation at break and toughness showed a contrary trend. The tensile strength of epoxy asphalt binder with 23.5 % oligomer was only 0.89 MPa, which was much lower than the specification required.